Analisis Pengaruh Bukaan Katup Terhadap Kapasitas dan Efisiensi Pompa Sentrifugal 3 Sudu pada 1600 RPM - Basuki Basuki; Mohammad Munib Rosadi; Retno Eka Pramitasari; Fajar Satriya Hadi; Dian Anisa Rokhmah Wati (Universitas Muhammadiyah Yogyakarta, 2024)
Fluid is a substance that is capable of flowing. The types of fluids that are often used in everyday life are liquid fluids and gas fluids. To drain the fluid you need a laundry device called a pump. The working principle of the pump is to provide pressure or energy to the fluid. This type of research is experimental research, namely, researchers carry out experiments to obtain data in the form of numbers or quantitative data. Researchers varied the valve openings from 0o, 25o, 45o, and 65o and used a pump rotation of 1600 RPM. This research plan is to determine the effect of valve opening on pump capacity and efficiency. The research results show that the pump capacity and efficiency results at valve openings from 0o to 65o have increased significantly. The greatest capacity and efficiency occur at 65o valve openings with a value of 6 L/M and 43.2%.